Conrad's shadow : catastrophe, mimesis, theory - Lawtoo, Nidesh (Michigan State University Press, 2016)
Lawtoo offers new readings of Joseph Conrad's novels and the postcolonial and cinematic works that respond to his oeuvre. Lawtoo argues that Conrad's fascination with doubles urges readers to reflect on the two sides of mimesis, that once joined, reveal Conrad's Janus-faced fictions as powerfully relevant to our contemporary world of global violence and environmental crisis.
Keywords: Conrad, Joseph, -- 1857-1924 -- Criticism and interpretation.; Conrad, Joseph, -- 1857-1924; LITERARY CRITICISM -- European -- English, Irish, Scottish, Welsh.; Criticism, interpretation, etc.